Military Perspectives on the Provision of Spiritual Care in the Australian Defence Force: A Cross-Sectional Study - Best, Megan (Journal of religion and health, 2024)
A module to explore perspectives on chaplaincy services was included in an online enterprise survey randomly distributed to members of the Australian Defence Force (ADF) during 2021. Up to eight questions were answered by 2783 active military personnel relating to their perception of chaplain activities and the impact of chaplaincy services. Of those military participants answering the question on religious status (n = 1116), a total of 71.6% (n = 799) of respondents identified as non-religious while 28.4% (n = 317) identified as holding a religious affiliation. Approximately 44.2% (n = 1230) of participants had sought support from a chaplain, of which 85.3% (n = 1049) found chaplaincy care to be satisfactory or very satisfactory. While the data suggest there is a lack of clarity around the multiple roles undertaken by chaplaincy, nevertheless respondents were just as likely to prefer chaplains for personal support (24.0%), as they were to seek help from non-chaplaincy personnel such as a non-ADF counsellor (23.2%), their workplace supervisor (23.1%) or a psychologist (21.8%). This evidence affirms that the spiritual care provided by military chaplaincy remains one of several preferred choices and thus a valued part of the holistic care provided by the ADF to support the health and wellbeing of its members.